Producing Gel With Various Ingredients: a Review - Marthin Rivai Hezekiel Siagian; Sayid Umar Abraham; Avido Yuliestyan (Program studi Teknik Kimia UNS, 2024)
Unhealthy fat choices in diets are linked to obesity and other health problems. The food industry faces a challenge to develop low-fat products that maintain desirable textures and functionalities. Food gels, semi-solid materials formed by small molecules or large organic molecules that can hold liquids, offer a promising approach for replacing fat in various food applications like yogurt, ice cream, and cheese. This review discusses recent research on: Types of biopolymers used for fat substitution in gels, including proteins, polysaccharides, and their combinations. The importance of rheological studies in understanding the characteristics of these fat-substituted gels. How manipulating rheological parameters can influence the texture and properties of food products.Keywords: Gel, Rheology, Fat, Protein, Polysaccharide